Metabolic risk in schoolchildren is associated with low levels of cardiorespiratory fitness, obesity, and parents' nutritional profile - Pâmela Ferreira Todendi; Andréia Rosane de Moura Valim; Cézane Priscila Reuter; Elza Daniel de Mello; Anelise Reis Gaya; Miria Suzana Burgos (Elsevier, 2016)
Objective: Verify the association between metabolic risk profile in students with different levels of cardiorespiratory fitness and body mass index, as well as the nutritional status of their parents. Methods: A cross-sectional study comprising 1.254 schoolchildren aged between seven and 17 years. The metabolic risk profile was calculated by summing the standardized values of high density lipoproteins and low density lipoproteins, triglycerides, glucose and systolic blood pressure. The parents' nutritional status was evaluated by self-reported weight and height data, for body mass index calculating. The body mass index of schoolchildren was classified as underweight/normal weight and overweight/obesity. The cardiorespiratory fitness was assessed by 9-minute running/walk test, being categorized as fit (good levels) and unfit (low levels). Data were analyzed using prevalence ratio values (PR). Results: The data indicates a higher occurrence of developing metabolic risk in schoolchildren whose mother is obese (PR: 1.50; 95% CI: 1.01, 2.23), and even higher for those whose father and mother are obese (PR: 2, 79, 95% CI: 1.41; 5.51). Students who have low levels of cardiorespiratory fitness and overweight/obesity have higher occurrence of presenting metabolic risk profile (PR: 5.25; 95% CI: 3.31; 8.16). Conclusion: the occurrence of developing metabolic risk in schoolchildren increase when they have low levels of cardiorespiratory fitness and overweight/obesity, and the presence of parental obesity. Resumo: Objetivo: Verificar se há associação entre o perfil de risco metabólico em escolares com diferentes níveis de aptidão cardiorrespiratória e índice de massa corporal, bem como com o perfil nutricional de seus pais. Métodos: Estudo transversal constituído por 1.254 escolares com idade entre sete e 17 anos. O perfil de risco metabólico foi calculado por meio da soma dos valores estandardizados de lipoproteína de alta densidade e lipoproteína de baixa densidade, triglicerídeos, glicose e pressão arterial sistólica. O perfil nutricional dos pais foi avaliado pelos dados autorreferidos de peso e estatura, calculando-se posteriormente o índice de massa corporal. O índice de massa corporal do escolar foi classificado em baixo peso/peso normal e sobrepeso/obesidade. A aptidão cardiorrespiratória foi avaliada através do teste de corrida/caminhada de 9 minutos, sendo categorizada em apto (bons níveis) e inapto (baixos níveis). Os dados foram analisados através dos valores de razão de prevalência (RP). Resultados: Os dados apontam maior ocorrência de desenvolvimento de risco metabólico em escolares que apresentam mãe com obesidade (RP: 1,50; IC 95%: 1,01; 2,23) e, maior ainda, em escolares que possuem pai e mãe obesos (RP: 2,79; IC 95%: 1,41; 5,51). Escolares que apresentam baixos níveis de aptidão cardiorrespiratória e sobrepeso/obesidade possuem maior ocorrência de perfil metabólico de risco (RP: 5,25; IC 95%: 3,31; 8,16). Conclusões: a ocorrência de desenvolvimento de risco metabólico em escolares aumentam quando estes apresentam baixos níveis de aptidão cardiorrespiratória e sobrepeso/obesidade, assim como na presença de obesidade dos pais. Keywords: School, Cardiorespiratory fitness, Body mass index, Parents, Palavras-chave: Escolares, Aptidão cardiorrespiratória, Índice de massa corporal, Pais